2016
DOI: 10.1007/s12094-016-1490-4
|View full text |Cite
|
Sign up to set email alerts
|

Consensus and controversies in the definition, assessment, treatment and monitoring of BTcP: results of a Delphi study

Abstract: IntroductionThere is no unanimous consensus on the clinical features to define breakthrough cancer pain (BTcP). The current project aimed to investigate the opinion of a panel of experts on cancer pain on how to define, diagnose, assess, treat and monitor BTcP.Materials and methodsA two-round Spanish multi-centre exploratory Delphi study was conducted with medical experts (n = 90) previously selected from Medical Oncology Services, Radiation Oncology, Palliative Care/Home Care Teams, and Pain Units. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 21 publications
1
29
0
7
Order By: Relevance
“…Nevertheless, most contemporary guidelines exclude end-of-dose pain/end-of-dose failure as a subtype of breakthrough pain, since this phenomenon represents a ‘failure’ of the around-the-clock/background medication 5–8. Moreover, there appears to be high agreement with this position among relevant healthcare professionals within Europe 9 10. In this study, 28% patients with breakthrough pain identified that ‘scheduled pain medication wearing off’ was a precipitant of their breakthrough cancer pain, which again suggests that many of these patients did not have adequately controlled background pain.…”
mentioning
confidence: 63%
“…Nevertheless, most contemporary guidelines exclude end-of-dose pain/end-of-dose failure as a subtype of breakthrough pain, since this phenomenon represents a ‘failure’ of the around-the-clock/background medication 5–8. Moreover, there appears to be high agreement with this position among relevant healthcare professionals within Europe 9 10. In this study, 28% patients with breakthrough pain identified that ‘scheduled pain medication wearing off’ was a precipitant of their breakthrough cancer pain, which again suggests that many of these patients did not have adequately controlled background pain.…”
mentioning
confidence: 63%
“…The experience in the management of patients with BTcP was shown to be >12 ± 7 years, with an average of > 400 patients attended during the last year. 36 (20.5%) out of the physicians recruited for the present study had also participated in the previous Delphi consensus study [8], and most of the sample (88.9%) was aware of the recommendations and (85.5%) considered them to be useful for their clinical daily practice. Table 1 shows the digital profile of the sample.…”
Section: Professional and Digital Profile Of Participantsmentioning
confidence: 99%
“…The idea was then creating a mobile application able to run in as a native app on various mobile platforms and operating systems (such as Android, iOS). App INES·DIO contents gathered the most significant results of a Spanish Delphi study about the consensus and controversies in the definition, assessment, treatment and monitoring of BTcP [8]. This application allows the physician to generate an individual patient register to be finally included (via email) in the clinical history.…”
Section: The App Ines·diomentioning
confidence: 99%
See 2 more Smart Citations